First Record of Simulium (Chirostilbia) (Diptera: Simuliidae) in the province of Buenos Aires, Argentina - Ordoqui, Eliana (2023)
Blackflies are dipterans that belong to the family Simuliidae, common inhabitants of lotic ecosystems. The present study reports the first record of Simulium (Chirostilbia) subpallidum Lutz for Buenos Aires, rising to eight registered species of blackflies in the province. This report represents, to date, the southernmost distribution detected for the species and subgenus in South America.